Examining the Effectiveness of Corporate E-Learning in Global Talent Management - Wong, Amy Ooi; Sixl-Daniell, Karin (International Journal of Advanced Corporate Learning (iJAC), 2017)
The purpose of this study is to examine the effectiveness of corporate e-learning in the context of talent management on a global scale. It begins with a discussion of the importance of talent management, the challenges in global talent management, and the role of corporate e-learning in global talent management. Data collected via an online survey from 74 students (global leaders from a multinational IT provider with more than 90,000 employees across 50 countries) enrolled in a customized corporate e-learning program is presented and discussed. The findings suggest that corporate e-learning can be used to develop talent attributes and skills such as problem solving, analytical, communication, research, and time management skills. Specifically, analytical, communication, and time management skills are important predictors of overall corporate e-learning experience, while analytical and research skills are important predictors of job performance. As part of global talent management, companies can enroll their A-players, high performers or high potentials into relevant corporate e-learning programs that can be used to effectively address the training challenges of a scattered workforce and improve coordination among internal and outside collaborators and partners in complex business processes and projects. The sample for this study was limited to a multinational IT services provider. Future research should extend the scope of data collection to include talents from a variety of organizations, as well as a variety of geographies and industries to further investigate the generalizability of these findings.